2014
DOI: 10.1155/2014/962343
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effect of Neurogenesis and Regulation of GSK3β/PP2A Expression in Acupuncture Treatment of Neural Functional Damage Caused by Focal Ischemia in MCAO Rats

Abstract: 170 SD rats were randomly divided to five groups. Rats in model group, no-acupuncture group, and acupuncture group were subjected to MCAO surgery. Acupuncture group received 3 consecutive acupuncture treatments at a parameter that deep in 2 mm towards apex nasi and thrust/lifted at 3 times per second for 1 minute, while model group and no-acupuncture group were no-intervention control groups. Serious neural functional damage and sharp decrease of cerebral blood flow, obvious infarction volume, increased nestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Selectively inhibition of GSK-3β may be neuroprotective (Guo et al, 2014;Kelly et al, 2004;Sun et al, 2011). Recent studies reported that GSK-3β at Ser9 was increased in MCAO model 3 or 5 days post ischemia Luo et al, 2014), while other reports showed that phosphorylation of GSK-3β at Ser9 was decreased after ischemia/reperfusion (Chern et al, 2014;Ma et al, 2014). One possible explanation for this discrepancy is the difference in ischemic time and the subregions where samples were collected.…”
Section: Discussionmentioning
confidence: 99%
“…Selectively inhibition of GSK-3β may be neuroprotective (Guo et al, 2014;Kelly et al, 2004;Sun et al, 2011). Recent studies reported that GSK-3β at Ser9 was increased in MCAO model 3 or 5 days post ischemia Luo et al, 2014), while other reports showed that phosphorylation of GSK-3β at Ser9 was decreased after ischemia/reperfusion (Chern et al, 2014;Ma et al, 2014). One possible explanation for this discrepancy is the difference in ischemic time and the subregions where samples were collected.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, images of the TTC-stained slices were captured using an Olympus FE-240 digital camera (Shanghai Pooher Photoelectric Technology Co., Ltd., Shanghai, China) and analyzed using ImagePro ® Plus 6.0 analysis software (Media Cybernetics, Inc., Rockville, MD, USA). The infarction volume was expressed as the infarction ratio (a percentage of the total ipsilateral hemispheric volume), which was calculated according to the following equation ( 31 , 32 ): [(contralateral hemispheric volume − ipsilateral hemispheric volume)/contra-lateral hemispheric volume] × 100%.…”
Section: Methodsmentioning
confidence: 99%
“…Quchi: promotes neuronal cell proliferation [ 23 , 24 , 26 , 27 , 28 ], activates PI3K/Akt pathways to prevent apoptosis [ 38 , 39 ], reduces ischemic brain damage through anti-inflammation [ 58 ] and improves metabolism in the affected area [ 60 ]. Shuigou: one of the most commonly used single acupoints, induces neurogenesis by stimulating the GSK3β/PP2A signaling pathway [ 63 ] and modulates the angiotensin system by reducing the expression of angiotensin II and AT1R, while also enhancing the expression of AT2R, which is related to angiogenic processes [ 32 ]. Dazhui: enhances the proliferation of neuronal stem cells [ 22 ], improves perfusion at the ischemic zone [ 31 ], and mediates anti-apoptotic pathways [ 40 , 43 , 46 ].…”
Section: Summary Of Main Acupoints Selected In the Reviewed Studiementioning
confidence: 99%